2021 IEEE International Conference on Cloud Engineering (IC2E) 2021
DOI: 10.1109/ic2e52221.2021.00014
|View full text |Cite
|
Sign up to set email alerts
|

BeFaaS: An Application-Centric Benchmarking Framework for FaaS Platforms

Abstract: Due to the popularity of the FaaS programming model, there is now a wide variety of commercial and open-source FaaS systems. Hence, for comparison of different FaaS systems and their configuration options, FaaS application developers rely on FaaS benchmarking frameworks. Existing frameworks, however, tend to evaluate only single isolated aspects, a more holistic application-centric benchmarking framework is still missing.In previous work, we proposed BeFaaS, an extensible application-centric benchmarking frame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…Serverless benchmarks and measurement frameworks: Table 3 compares ServiBench with the most important serverless benchmarks and performance frameworks. Our study (i) has a wider scope with more applications, functions, and services, and in particular with more than one function or service, (ii) adds realistic applications and invocation patterns based on real-world characteristics [22,66,84], (iii) does not rely on low-level, server-side tracing, not available for public serverless platforms, and (iv) enables analysis across a variety of situations common in production, including synchronous Reference Focus Scope Invocation Patterns Insights apps func/app micro langs services concurrent trace-based white box async faas-profiler [65] Server-level overheads 5 1 28 2 0 vHive [73] Cold-start breakdown 9 1 0 1 1 ServerlessBench [86] Diverse test cases 4 1-7 10 4 1 SeBS [14] Memory size impact 10 1 0 2 1 FunctionBench [34] Diverse workloads 8 1 6 1 1 FaaSDom [46] Language comparison 0 -5 4 0 BeFaaS [27] Application-centric 1 17 0 1 1…”
Section: Related Workmentioning
confidence: 99%
“…Serverless benchmarks and measurement frameworks: Table 3 compares ServiBench with the most important serverless benchmarks and performance frameworks. Our study (i) has a wider scope with more applications, functions, and services, and in particular with more than one function or service, (ii) adds realistic applications and invocation patterns based on real-world characteristics [22,66,84], (iii) does not rely on low-level, server-side tracing, not available for public serverless platforms, and (iv) enables analysis across a variety of situations common in production, including synchronous Reference Focus Scope Invocation Patterns Insights apps func/app micro langs services concurrent trace-based white box async faas-profiler [65] Server-level overheads 5 1 28 2 0 vHive [73] Cold-start breakdown 9 1 0 1 1 ServerlessBench [86] Diverse test cases 4 1-7 10 4 1 SeBS [14] Memory size impact 10 1 0 2 1 FunctionBench [34] Diverse workloads 8 1 6 1 1 FaaSDom [46] Language comparison 0 -5 4 0 BeFaaS [27] Application-centric 1 17 0 1 1…”
Section: Related Workmentioning
confidence: 99%
“…Function infras-tructure is completely handled by the cloud service provider, i.e., "serverless", and consumers pay per request based on the resources consumed by a function [12,22]. Functions can be implemented in a number of programming languages and can be invoked by web requests, IoT sensor readings, database updates, and even other functions, so-called function chaining [23,24].…”
Section: Function-as-a-servicementioning
confidence: 99%
“…Although including a cost model in cloud benchmarking studies is considered good scientific practice [37], in existing benchmarking studies on FaaS [24,[38][39][40][41] and DSP [4,42,43], cost evaluations can mainly be found for cloud functions, where the pay-perexecution pricing model has presented a significant paradigm shift.…”
Section: Related Workmentioning
confidence: 99%
“…In serverless computing, developers rely on managed cloud platform services as application building blocks which are connected through application-specific glue code. Usually, this glue code is written as sequences of small, stateless functions [3,4] -often invoked in an event-driven modelrunning on top of Function-as-a-Service (FaaS) platforms such as AWS Lambda 1 or Google Cloud Functions 2 .…”
Section: Introductionmentioning
confidence: 99%
“…In this section, we give a brief overview of FaaS as a paradigm, discuss influence factors on performance and cost, and finally function fusion as a concept. FaaS is a popular paradigm for cloud software development and deployment in which developers write their source code in the form of small, stateless functions 3 and leave all operations aspects to the cloud provider. These functions are usually written in highlevel programming languages such as Node.js [10].…”
Section: Introductionmentioning
confidence: 99%